2020
DOI: 10.1080/1540496x.2020.1784719
|View full text |Cite
|
Sign up to set email alerts
|

Country Responses and the Reaction of the Stock Market to COVID-19—a Preliminary Exposition

Abstract: As the coronavirus pandemic (COVID-19) has amplified so has country responses to it. With COVID-19 taking its toll on humans, as reflected in the number of people infected by, and deaths from, COVID-19, countries responded by locking down economic activity and peoples movement, imposing travel bans, and implementing stimulus packages to cushion the unprecedented slowdown in economic activity and loss of jobs. This article provides a commentary on how the most active financial indicator-namely, the stock price-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
373
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 571 publications
(459 citation statements)
references
References 12 publications
29
373
1
4
Order By: Relevance
“…Our finding of a pandemic-induced economic uncertainty in China and Korea echoes the observations that the unprecedented nature of the COVID-19 outbreak spearheaded equally unprecedented policy responses (Iyke, 2020b;Phan & Narayan, 2020), whose paths and impacts are uncertain (Altig et al, 2020). Our conclusion is in line with Altig et al (2020), who find, using the UK and the US data, that the implied economic uncertainty of the COVID-19 shock is large.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Our finding of a pandemic-induced economic uncertainty in China and Korea echoes the observations that the unprecedented nature of the COVID-19 outbreak spearheaded equally unprecedented policy responses (Iyke, 2020b;Phan & Narayan, 2020), whose paths and impacts are uncertain (Altig et al, 2020). Our conclusion is in line with Altig et al (2020), who find, using the UK and the US data, that the implied economic uncertainty of the COVID-19 shock is large.…”
Section: Resultssupporting
confidence: 88%
“…We measure the COVID-19 pandemic using a dummy variable, which assigns a value of zero to months before March 2020 and a value of one from March 2020. On 11 th March 2020, the World Health Organization declared COVID-19 as a pandemic (see Phan & Narayan, 2020). Hence, March 2020 is chosen to coincide with this declaration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Markets are a function of government, hence responding reliant on authority reply [84]. Alfaro, Chari, Greenland and Schott [32] confirmed that a doubling of projected contaminations is linked with a 4 to 11 percent deterioration of aggregate market value.…”
Section: Earlier Studies Towards the Impact Of Covid-19 On Stock Marketsmentioning
confidence: 97%
“…The existing literature on the impact of COVID-19 is evolving. The literature has found that the pandemic adversely impacts economic growth and trade (Vidya & Prabheesh, 2020) and stock markets (Ertuğrul et al, 2020;Haroon & Rizvi, 2020;He et al, 2020;Huang & Zheng, 2020;Iyke, 2020;Phan & Narayan, 2020;. However, no specific study examines the FPI and stock market returns relationship during the COVID-19 pandemic.…”
Section: Introduction I Introductionmentioning
confidence: 99%